Could we advance the science of religion (better) without the concept "religion"? - Barrett, Justin L. (Religion, brain & behavior, 2017)
Could it be that scientific progress in the study of cultural experience and expression that we usually label "religion" would be accelerated if we dropped religion as an organizing concept? This question is raised in relation to several related queries: whether scientific approaches to the study of religion suffer marginalization in part because of conceptual confusion over the concept religion; whether progress in measurement in the study of religious cultural expression has been hindered by adherence to religion and its derivatives as guiding concepts; and whether partisanship in this academic area may be encouraged by poor conceptual hygiene concerning religion.